Evangelicalism and Conflict in Northern Ireland - Ganiel, G. author. aut Link
XVI, 207 p.
Keywords: This innovative book explores the role of evangelical religion in the conflict in Northern Ireland, including how it may contribute to a peaceful political transition. Ganiel offers an original perspective on the role of a 'strong' religion in conflict transformation, and the misunderstood role of evangelicalism in the process.